Metallic Micro‐Nano Network‐Based Soft Transparent Electrodes: Materials, Processes, and Applications - Liyang Chen (6279566) (2023)
Soft transparent electrodes (TEs) have received tremendous interest from academia and industry due to the rapid development of lightweight, transparent soft electronics. Metallic micro‐nano networks (MMNNs) are a class of promising soft TEs that exhibit excellent optical and electrical properties, including low sheet resistance and high optical transmittance, as well as superior mechanical properties such as softness, robustness, and desirable stability. They are genuinely interesting alternatives to conventional conductive metal oxides, which are expensive to fabricate and have limited flexibility on soft surfaces. This review summarizes state‐of‐the‐art research developments in MMNN‐based soft TEs in terms of performance specifications, fabrication methods, and application areas. The review describes the implementation of MMNN‐based soft TEs in optoelectronics, bioelectronics, tactile sensors, energy storage devices, and other applications. Finally, it presents a perspective on the technical difficulties and potential future possibilities for MMNN‐based TE development. Other Information Published in: Advanced Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/advs.202302858